Computing Fluid-Structure Interaction by the Partitioned Approach with Direct Forcing (Communications in Computational Physics, 2018)
In this paper, we propose a new partitioned approach to compute fluid-structureinteraction (FSI) by extending the original direct-forcing technique and integratingit with the immersed boundary method. The fluid and structural equations arecalculated separately via their respective disciplinary algorithms, with the fluid motionsolved by the immersed boundary method on a uniform Cartesian mesh and thestructural motion solved by a finite element method, and their solution data only communicateat the fluid-structure interface. This computational framework is capable ofhandling FSI problems with sophisticated structures described by detailed constitutivelaws. The proposed methods are thoroughly tested through numerical simulations involvingviscous fluid flow interacting with rigid, elastic solid, and elastic thin-walledstructures.